Betawi Laksa As A Cultural Culinary Tourist Attraction In Jakarta: The Role Of Product Quality And Consumer Perceptions - Adella Syahrany Rosdianti; B. Syarifuddin Latif (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
This study aims to analyse the role of product quality and consumer perception in sustaining   Betawi Laksa as a cultural culinary tourism attraction in Jakarta. A qualitative approach with a case study method was employed, involving seven informants consisting of consumers and culinary practitioners. Data were collected through in-depth interviews and documentation, and analysed using data reduction, data display, and conclusion drawing techniques. The findings reveal that product quality, particularly authentic taste, is the main strength of Betawi Laksa, while consumer perception tends to be positive but not yet translated into consistent consumption behaviour. This indicates a gap between perception and actual consumption. Furthermore, external factors such as modern culinary trends, visual appeal, and limited promotion influence consumer preferences. The study highlights the importance of balancing intrinsic values (authenticity and cultural meaning) with extrinsic values (presentation, accessibility, and promotion). This research contributes to culinary tourism studies by proposing an integrative perspective between cultural preservation and adaptive innovation in traditional food development.